"Anxiety and Type 1 diabetes are like cousins": The experience of anxiety symptoms in youth with Type 1 diabetes. Issue 6 (30th October 2018) - Rechenberg, Kaitlyn; Grey, Margaret; Sadler, Lois
Abstract : Type 1 diabetes (T1D) is one of the most common chronic health conditions in youth in the United States, and its incidence is rising worldwide. Youth with T1D are at a high risk of psychological comorbidity, for example, anxiety, depression, and eating disorders. Psychological comorbidities, especially anxiety symptoms, have been correlated with poorer diabetes outcomes, but anxiety symptoms have not been well studied in these youth. The primary aim of this study was to describe the experience of anxiety symptoms in youth with T1D, especially as those symptoms relate to diabetes self‐management tasks. We used a qualitative descriptive approach, consisting of an in‐depth, semi‐structured interview comprising 10 open‐ended questions with follow‐up probes. The analysis was guided by the principles of thematic analysis. Demographic data, Hemoglobin A1c levels, and the State‐Trait Anxiety Inventory for Children survey data were also collected and analyzed. We identified four themes and seven sub‐themes. Participants ( n  = 29, ages 10–16, 55% female) reported that T1D was an extra layer of responsibility that took time away from their ability to participate fully in other aspects of their lives. Some participants were able to integrate diabetes management into their lives, while others were not. Some participants were dependent on parents and the school nurse for diabetes management. Participants described two types of anxiety symptoms, general and diabetes‐specific, and they noted that their experience of anxiety was associated with poor quality sleep, general lifestyle factors, and diabetes.